Gold nanoparticle-catalysed functionalization of carbon–hydrogen bonds by carbene transfer reactions. Issue 13 (14th March 2022) - Martínez-Laguna, Jonathan; Mollar-Cuni, Andrés; Ventura-Espinosa, David; Martín, Santiago; Caballero, Ana; Mata, Jose A.; Pérez, Pedro J.
Abstract : Gold nanoparticles stabilized by NHC ligands and supported onto reduced graphene oxide (rGO) catalyse the functionalization of cyclohexane and benzene C–H bonds upon insertion of carbene CHCO2 Et (from N2 CHCO2 Et) groups. Abstract : Gold nanoparticles stabilized by NHC ligands and supported onto reduced graphene oxide (rGO) catalyse the functionalization of cyclohexane and benzene C–H bonds upon insertion of carbene CHCO2 Et (from N2 CHCO2 Et) groups. This is the first example in which such Csp3 -H or Csp2 -H bonds are functionalized with this strategy with nanoparticulated gold. This Au-NP@rGO material shows an exceptional activity, providing TON values 5–10 times higher than those already reported for molecular gold catalysts. Recyclability is also effective, reaching an accumulated TON value of 1400 after six consecutive uses.